Physiological Indicators and Production Performance of Dairy Cows With Tongue Rolling Stereotyped Behavior - Sun, Fuyu; Zhao, Qingyao; Chen, Xiaoyang; Zhao, Guangyong; Gu, Xianhong (Frontiers in Veterinary Science, 2022)
Non-nutritive oral behaviors, especially tongue rolling, are prevalent in the stabled cow population. These behaviors mean that the environment or management process might not suit the cows, suggesting low welfare. However, few researches have reported the physiological indicators or production performance of dairy cows with the stereotyped behavior. This study aimed to determine physical conditions, daily activity, rumen fermentation, and milk production of cows with tongue-rolling behavior. 359 Holstein cows in the same barn and lactation stage were subjected to scan sampling behavior observations 126 times for 7 days. 10 cows with high-frequency tongue-rolling behavior (TON) and 10 cows without abnormal oral behavior (CON) were selected for further study. Serum sample, ruminal fluid, milk sample, and behavior record video of TON and CON cows were collected. TON cows had more drinking behavior and more stable lying behavior than the CON cows during the daytime. The body condition score of the TON cows decreased, while the milk yield, yield of milk fat, protein, and lactose in the study period increased. The TON cows had lower ruminal fluid pH, acetate/propionate ratio, and total volatile acid. The bacterial diversity in the ruminal fluid was not different between the two groups. Compared to CON cows, the TON cows had a higher level of serum stress indicators, such as cortisol, thyroid hormone, and norepinephrine, which positively correlated to the frequency of tongue-rolling behavior. Meanwhile, the TON cows had a higher level of lactate dehydrogenase, serum glucose, total triglyceride, total cholesterol, and Interleukin 6. Overall, it means they suffer from higher levels of stress and have higher energy metabolism for a long time when cows show tongue-rolling behavior. TON cows had suffered a higher stress level and had higher energy metabolic status for a long time. The TON cows might have better heat tolerance to the thermal environment by more lying and drinking time. Our data revealed the changes in milk production, physiological stress indicators of dairy cows with high-frequency tongue rolling behavior, which will provide essential knowledge for the in-depth understanding of tongue rolling behavior in dairy cows.